Educação ambiental crítica na formação inicial de pedagogos: contribuições a partir do uso de um material de apoio pedagógico - Brustolin, Ângela Camila (2024)
Environmental Education (EE), according to Law 9.795/99, must be included at all levels of education, in a continuous, transversal and multidisciplinary manner. The inclusion of EE in the initial and continuing education of teachers is essential for it to be addressed and effectively developed in the environment. Thus, the research theme of this thesis was EE in the initial education of teachers, specifically pedagogues. Some research studies that address the inclusion of environmental issues in the initial education of teachers have been developed within the scope of different undergraduate courses - pedagogy being one of the most investigated - and highlight the need to address these issues more clearly, since this often happens in a very technical disciplinary structure. Thus, based on these reflections, the question that will guide the development of this thesis was defined: To what extent does critical EE reveal itself and support the teaching practices of pedagogues in initial education? In this sense, the general objective of this work was to develop an educational booklet on the topic of EE, with the intention that this material would serve as a theoretical and practical support and encourage pedagogues in initial training to reflect on their teaching practice. The investigative process was characterized by a qualitative approach, and the subjects investigated were teachers and students of the Pedagogy course defined for the study. The instruments for data collection were document analysis, application of questionnaires and interviews. For data analysis, Textual Discursive Analysis and the IRaMuTeQ software were used. Once the collected data were systematized and understood, the development of the educational product (EP) linked to this thesis (EE Booklet) began, which was implemented throughout the development of the EE training course. In the EA booklet, students found several topics, such as: the laws that guide the implementation of EA - especially the National EA Policy -, different EA trends, flora, water, solid waste, among others. The EA training course was designed taking into account the answers obtained in the questionnaires and interviews and was developed in five modules, with different themes and objectives, in order to present and discuss the theme of EA, creating a space for the exchange of ideas and proposals and actions towards the implementation (insertion) of EA in this context. In the end, an evaluation carried out allowed us to understand that the EA training course was judged very positively by the participating students, who also highlighted that the topics covered throughout the course were seen as relevant to their initial training. In addition, they pointed out that EA should be more present in the academic environment, and that the Pedagogy course should cover the topic in a more in-depth and constant manner. Regarding the PE, it was considered that it achieved its objective of being a material that talks about EA and that serves as pedagogical support for both pedagogues in initial training and teachers who are already working, especially those in elementary education. The students highly praised the material, characterizing it as very well organized, with simple and easy-to-understand language, with a pleasant layout and unanimously approved content and concepts. During the PE evaluation, the academics also highlighted the importance of EA in the training of pedagogues and recognized the support that the PE will give them in their internship practices and even in the final course work. It is hoped that the results of this work can contribute to the reflection on how much the effective insertion of EE in teacher training curricula, and specifically in Pedagogy courses, is urgent and necessary, and on how much this can help to build a more complex, critical and participatory education. The SP linked to this thesis is available on the website of the Graduate Program in Science and Mathematics Teaching at the University of Passo Fundo and on the Educapes website https://educapes.capes.gov.br/handle/capes/918013.